A composite catalyst g-c3n4 / zn for photoanode 0.4 Ni 0.6 Preparation method of fe2o4 / biobr
Patent Information
- Application Number
- CN202310764085.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
[0004]本发明针对BiOBr带隙较窄、可见光利用率低、综合性能受限的问题,制备了一种用作光催化燃料电池阳极的g-C3N4/BiOBr/Zn0.4Ni0.6Fe2O4复合光催化剂,有效改善了BiOBr的性能缺陷,拓展BiOBr基光催化剂的应用,测试了处理RhB溶液和页岩气返排水的产电参数
[0012](1)本发明方法制备的g-C3N4/Zn0.4Ni0.6Fe2O4/BiOBr复合光催化剂具有较高的光催化活性。在300W模拟太阳光的氙灯照射下,0.1g制备的最优光催化剂分散于100mL浓度为10mg/L罗丹明B溶液中,光照30min降解率达到了99.79%。降解速率和降解率均优于对比文件1。
Smart Images

Figure CN116845260B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr belongs to the field of inorganic catalytic materials technology. Background Technology
[0002] Photocatalytic fuel cell technology features mild reaction conditions, relatively non-toxic products, and the ability to fully utilize the chemical energy of pollutants in organic wastewater. Its core lies in the performance of the semiconductor photocatalyst, which serves as the photoanode. Bismuth oxyhalides possess advantages such as good chemical stability, good thermal stability, and low cost, and are widely used in the photocatalytic degradation of wastewater. Among them, bismuth oxybromine (BiOBr) exhibits characteristics such as visible light responsiveness and favorable valence and conduction band positions, demonstrating better performance than bismuth oxychloride and bismuth oxyiodide. However, the relatively large band gap of BiOBr limits its application and development in the field of photocatalysis. Semiconductor composites can enhance visible light utilization by constructing heterojunctions, while also promoting the separation and transfer of photogenerated electrons to improve overall performance. g-C3N4 and Zn 0.4 Ni 0.6 Fe2O4 is a semiconductor photocatalyst with a narrow band gap. Its excellent visible light reactivity can effectively improve the defects of photocatalysts during composite modification. It has been widely used by researchers for semiconductor modification, which provides a basis for the design of g-C3N4 and Zn... 0.4 Ni 0.6 The synergistic modification of BiOBr with Fe2O4 makes it possible to prepare efficient photocatalytic fuel cell anode materials.
[0003] Currently, there are many research results on the modification of BiOBr. For example, the article "Preparation of g-C3N4 / CeO2 / BiOBr three-phase composite material and its performance in visible light photocatalytic degradation of RhB" in "Materials Engineering", Vol. 51, No. 2, 2023 (comparative document 1) prepared g-C3N4 / CeO2 / BiOBr by precipitation method. This method uses ethanol as solvent. First, a composite of CeO2 and BiOBr was prepared. Then, g-C3N4 and CeO2 / BiOBr were ultrasonically mixed for two hours using ethanol as solvent. After heating at 80℃ for 18 hours, the g-C3N4 / CeO2 / BiOBr three-phase composite material was finally obtained. The shortcomings of this method are: (1) Anhydrous ethanol needs to be added to prepare the precursor sol, which will increase the preparation cost and make it difficult to promote its use on a large scale; (2) Urea and thiourea are used as raw materials in the preparation of g-C3N4, which increases the factor of air pollution; (3) A large amount of rare earth element cerium (Ce, with the best degradability when the molar ratio with Br is 1:1) is involved in the preparation of CeO2 / BiOBr, which leads to high cost and is not suitable for promotion and application. For example, "Carbon Letters", Vol. 33, 2023, pp. 847-862, reported "Performance study of g-C3N4 / carbonblack / BiOBr@Ti3C2 / MoS2 photocatalytic fuel cell for the synergistic degradation of different types of pollutants" (reference document 2). This study constructed a photocatalytic fuel cell (PFC) to degrade TCH and RhB solutions using g-C3N4 / carbonblack / BiOBr as the anode and Ti3C2 / MoS2 as the cathode. g-C3N4 was first prepared by calcining melamine, and then added to a BiOBr precursor solution using a solvothermal method to prepare g-C3N4 / BiOBr. The g-C3N4 / BiOBr and carbon black were then dispersed in silica sol to form a uniform gel solution, which was then rapidly coated onto a carbon brush and dried to serve as the PFC anode, g-C3N4 / carbonblack / BiOBr.The shortcomings of this method are: (1) The preparation process of g-C3N4 / BiOBr uses hexadecyltrimethylammonium bromide as the bromine source and isopropanol and ethylene glycol as solvents. All three are organic compounds, which increases the preparation cost and safety risks, making it difficult to promote and use on a large scale; (2) Without considering the cathode material, the material preparation process is complicated and difficult to apply in actual engineering; (3) From the ratio of g-C3N4:carbon black:BiOBr in the anode material, the degradation effect of RhB is best at 2:1:1, but overall it is not much different from 1:1:1, 1:1:2 and g-C3N4, carbon black and BiOBr alone as anodes, which means that the degradation effect is not significant when g-C3N4 is modified by carbon black and BiOBr; (4) The power generation parameters have not been tested and studied. There are currently no literature reports on the use of PFC to treat shale gas backflow wastewater for power generation. Summary of the Invention
[0004] This invention addresses the limitations of BiOBr, such as narrow bandgap, low visible light utilization, and restricted overall performance, by preparing a g-C3N4 / BiOBr / Zn anode for use in photocatalytic fuel cells. 0.4 Ni 0.6 The Fe2O4 composite photocatalyst effectively improves the performance defects of BiOBr, expands the application of BiOBr-based photocatalysts, and tests the power generation parameters for treating RhB solution and shale gas backflow water. This preparation process is simple, requires few equipment, is low-cost, and produces a composite photocatalyst with high activity. The composite photocatalyst of this invention is g-C3N4 / Zn. 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows:
[0005] (1) Preparation of g-C3N4
[0006] Weigh 15g of melamine into a crucible and place it in a muffle furnace at 5℃·min. -1 The temperature was increased to 550℃ and held for 2 hours. After the heating was completed, the temperature was naturally cooled to room temperature and removed to obtain pale yellow g-C3N4.
[0007] (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4
[0008] 2.164 g FeCl3·6H2O, 0.5705 g NiCl2·6H2O, and 0.2181 g ZnCl2 were added to 50 mL of deionized water and sonicated for 30 min to obtain a yellow-green transparent solution A. 4 g NaOH was added to 50 mL of deionized water and sonicated for 5 min. The resulting NaOH solution was then slowly added dropwise to solution A under magnetic stirring until the pH reached 12. Stirring continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL reactor and hydrothermally treated at 180 °C for 12 h. After the reaction was complete, the mixture was allowed to cool naturally to room temperature and then filtered. The filter cake was washed with anhydrous ethanol and deionized water until the filtrate was neutral. The filtered cake was then dried and ground to obtain a brownish-red ZnCl2. 0.4 Ni 0.6 Fe2O4 powder.
[0009] (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr
[0010] Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.0152–0.1064g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn. 0.4 Ni 0.6 Fe2O4 / BiOBr.
[0011] The present invention adopts the above technical solution, and has the following main effects:
[0012] (1) g-C3N4 / Zn prepared by the method of the present invention 0.4 Ni 0.6 The Fe2O4 / BiOBr composite photocatalyst exhibits high photocatalytic activity. Under 300W simulated sunlight xenon lamp irradiation, 0.1g of the optimally prepared photocatalyst dispersed in 100mL of a 10mg / L Rhodamine B solution achieved a degradation rate of 99.79% after 30 minutes of illumination. Both the degradation rate and degradation rate are superior to those in reference document 1.
[0013] (2) g-C3N4 / Zn prepared by the method of the present invention0.4 Ni 0.6 A photocatalytic fuel cell constructed by loading Fe2O4 / BiOBr onto a stainless steel mesh as the anode and a platinum sheet as the cathode exhibits good power generation capacity. Using 10 mg / L Rhodamine B as the substrate, the degradation rate is 93.76% after 45 minutes, with an open-circuit voltage, short-circuit current density, and maximum output power density of 210.5 mV and 2.7 mA / m², respectively. 2 and 0.063mW / m 2 When shale gas backflow wastewater with 1 mmol / L potassium persulfate added was used as the substrate, the open-circuit voltage, short-circuit current density, and maximum output power density were 339.8 mV, 50.9 mA / m, and 1 mmol / L, respectively. 2 and 3.05mW / m 2 The composite catalyst supported on the PFC constructed as the anode in this invention can generate electricity while degrading pollutants in wastewater, and is generally superior to prior art document 2.
[0014] (3) The present invention is prepared by hydrothermal method, which is simple in preparation process, requires less equipment and has low cost. Attached Figure Description
[0015] Figure 1 For BiOBr and g-C3N4 / Zn 0.4 Ni 0.6 X-ray diffraction pattern of Fe2O4 / BiOBr
[0016] Figure 2 For BiOBr and g-C3N4 / Zn 0.4 Ni 0.6 XPS plot of Fe2O4 / BiOBr
[0017] Figure 3 For g-C3N4 / Zn 0.4 Ni 0.6 The degradation rate, current-voltage curves, and power density curves of the photocatalytic fuel cell using Fe2O4 / BiOBr as the anode and 10 mg / L Rhodamine B as the substrate are presented.
[0018] Figure 4 For g-C3N4 / Zn 0.4 Ni 0.6 Current-voltage curves and power density curves of a photocatalytic fuel cell using Fe2O4 / BiOBr as the anode and shale gas backflow wastewater with 1 mmol / L bisulfate added as the substrate. Detailed Implementation
[0019] The present invention will be further described below with reference to specific embodiments.
[0020] Example 1
[0021] A photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows:
[0022] (1) Preparation of g-C3N4
[0023] Weigh 15g of melamine into a crucible and place it in a muffle furnace at 5℃·min. -1 The temperature was increased to 550℃ and held for 2 hours. After the heating was completed, the temperature was naturally cooled to room temperature and removed to obtain pale yellow g-C3N4.
[0024] (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4
[0025] 2.164 g FeCl3·6H2O, 0.5705 g NiCl2·6H2O, and 0.2181 g ZnCl2 were added to 50 mL of deionized water and sonicated for 30 min to obtain a yellow-green transparent solution A. 4 g NaOH was added to 50 mL of deionized water and sonicated for 5 min. The resulting NaOH solution was then slowly added dropwise to solution A under magnetic stirring until the pH reached 12. Stirring continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL reactor and hydrothermally treated at 180 °C for 12 h. After the reaction was complete, the mixture was allowed to cool naturally to room temperature and then filtered. The filter cake was washed with anhydrous ethanol and deionized water until the filtrate was neutral. The filtered cake was then dried and ground to obtain a brownish-red ZnCl2. 0.4 Ni 0.6 Fe2O4 powder.
[0026] (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr
[0027] Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.0152g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn.0.4 Ni 0.6 Fe2O4 / BiOBr(1-CZNB-1).
[0028] Example 2
[0029] A photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows:
[0030] (1) Preparation of g-C3N4
[0031] Same as step (1) in Example 1.
[0032] (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4
[0033] Same as step (2) in Example 1.
[0034] (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr
[0035] Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.0457g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn. 0.4 Ni 0.6 Fe2O4 / BiOBr(1-CZNB-3).
[0036] Example 3
[0037] A photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows:
[0038] (1) Preparation of g-C3N4
[0039] Same as step (1) in Example 1.
[0040] (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4
[0041] Same as step (2) in Example 1.
[0042] (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr
[0043] Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.076g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn. 0.4 Ni 0.6 Fe2O4 / BiOBr(1-CZNB-5).
[0044] Example 4
[0045] A photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows:
[0046] (1) Preparation of g-C3N4
[0047] Same as step (1) in Example 1.
[0048] (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4
[0049] Same as step (2) in Example 1.
[0050] (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr
[0051] Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.1064g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn. 0.4 Ni 0.6 Fe2O4 / BiOBr(1-CZNB-7).
[0052] Experimental results
[0053] Example 2: The composite photocatalyst g-C3N4 / Zn 0.4 Ni 0.6 Fe2O4 / BiOBr exhibits the best catalytic degradation activity. For comparison, BiOBr samples were prepared. The BiOBr preparation method is the same as step (3) in Example 2, without the addition of g-C3N4 and Zn. 0.4 Ni 0.6 Fe2O4.
[0054] BiOBr's XRD pattern is as follows Figure 1 As shown in (a), the diffraction peaks of BiOBr at 2θ = 10.90°, 21.92°, 25.15°, 31.69°, 32.22°, 33.13°, 44.69° and 50.67° are consistent with the standard card JCPDS No. 09-0393, indicating that the present invention has prepared BiOBr with high purity, no impurities and good crystallinity by hydrothermal method.
[0055] XRD diffraction of composite photocatalysts as follows Figure 1 As shown in (b)-(e), g-C3N4 / Zn 0.4 Ni 0.6 In the Fe2O4 / BiOBr composition, the diffraction peaks belonging to BiOBr still correspond one-to-one with those of pure BiOBr, and the diffraction peaks are sharp and free of impurities, indicating that the prepared ternary composite sample has high purity and is free of impurities. Zn 0.4 Ni 0.6 The (220) and (311) crystal planes of Fe2O4 can be observed at 30.14° and 35.5° in the spectrum. The characteristic peaks of g-C3N4 were not observed due to the low doping concentration. In conclusion, the sample composite was successful.
[0056] The full X-ray photoelectron spectroscopy (XPS) spectrum of 1-CZNB-3 is shown below. Figure 2 As shown, the sample contains Bi, O, Br, C, N, Fe, Ni, and Zn elements. The peak at 284.19 eV in the fine spectrum of C1s corresponds to a C-C bond, the peak at 285.91 eV corresponds to a CN bond, and the peak at 288.05 eV corresponds to an NC=N bond. The three characteristic peaks in the fine spectrum of N1s are C=NC, sp in CNH, and sp in N1s. 2 The hybrid N and the π bond in the heterocyclic ring are located at 398.62 eV, 400.67 eV, and 404.21 eV, respectively. (From...) Figure 2 (g) It can be seen that there are two characteristic peaks of Fe 2p, which correspond to the Fe 2p3 / 2 orbital and the Fe 2p1 / 2 orbital, respectively, indicating that Fe exists in the +3 state in the complex. Figure 2 (h) and Figure 2 (i) are high-resolution spectra of Ni and Zn, respectively. The elemental peak signals of Ni and Zn in the spectra are relatively weak, which is due to the fact that Zn... 0.4 Ni 0.6 This is due to the very low Fe2O4 doping ratio (only 3% wt). From an elemental perspective, this demonstrates the successful synthesis of the composite sample.
[0057] When testing the performance of the composite photocatalytic material using Rhodamine B solution, it was found that 1-CZNB-3 prepared in Example 2 had the best effect. After 30 min of illumination, the degradation rate of 10 mg / L Rhodamine B solution reached 99.79%. Therefore, it was selected as the anode material for photocatalytic fuel cells.
[0058] A photocatalytic fuel cell using 1-CZNB-3 as the anode material and platinum sheet as the cathode, when irradiated by a 300W Xe lamp simulating sunlight, degrades a 10 mg / L Rhodamine B solution (…). Figure 3 The degradation rate after 45 minutes was 93.76%, and its open-circuit voltage, short-circuit current density, and maximum output power density were 210.5 mV, 2.7 mA / m, and 2.7 mA / m, respectively. 2 and 0.063mW / m 2 .
[0059] A photocatalytic fuel cell constructed using 1-CZNB-3 as the anode material and platinum sheet as the cathode, under simulated sunlight irradiation with a 300W Xe lamp, using shale gas backflow wastewater with 1 mmol / L potassium persulfate added as the substrate ( Figure 4 The open-circuit voltage, short-circuit current density, and maximum output power density are 339.8 mV, 50.9 mA / m, and 339.8 mV, 50.9 mA / m, respectively. 2 and 3.05mW / m2 。
Claims
1. A photoanode composite catalyst g-C3N4 / Zn 0.4 Ni 0.6 The preparation method of Fe2O4 / BiOBr is as follows: (1) Preparation of g-C3N4 Weigh 15g of melamine into a crucible and place it in a muffle furnace at 5℃·min. -1 The temperature was increased to 550℃ and held for 2 hours. After the heating was completed, the temperature was naturally cooled to room temperature and removed to obtain pale yellow g-C3N4. (2)Zn 0.4 Ni 0.6 Hydrothermal preparation of Fe2O4 2.164 g FeCl3·6H2O, 0.5705 g NiCl2·6H2O, and 0.2181 g ZnCl2 were added to 50 mL of deionized water and sonicated for 30 min to obtain a yellow-green transparent solution A. 4 g NaOH was added to 50 mL of deionized water and sonicated for 5 min. The resulting NaOH solution was then slowly added dropwise to solution A under magnetic stirring until the pH reached 12. Stirring continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL reactor and hydrothermally treated at 180 °C for 12 h. After the reaction was complete, the mixture was allowed to cool naturally to room temperature and then filtered. The filter cake was washed with anhydrous ethanol and deionized water until the filtrate was neutral. The filtered cake was then dried and ground to obtain a brownish-red ZnCl2. 0.4 Ni 0.6 Fe2O4 powder; (3)g-C3N4 / Zn 0.4 Ni 0.6 Preparation of Fe2O4 / BiOBr Weigh out 2.4249g Bi(NO3)3·5H2O, 0.0152g g-C3N4, and 0.0152–0.1064g Zn. 0.4 Ni 0.6 Fe₂O₄ was dispersed in 40 mL of deionized water and sonicated for 30 min to obtain suspension B. 0.5144 g of NaBr was dissolved in 20 mL of deionized water, and the resulting NaBr solution was slowly added dropwise to suspension B. Mechanical stirring was continued for 1 h to obtain the precursor solution. The precursor solution was transferred to a 100 mL polytetrafluoroethylene-lined container, placed in a reaction vessel, and hydrothermally heated at 140 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature, filtered, and the filter cake was repeatedly washed with deionized water and anhydrous ethanol until the filtrate was neutral. The cake was then dried at 60 °C for 12 h to obtain a light red powder, g-C₃N₄ / Zn. 0.4 Ni 0.6 Fe2O4 / BiOBr.
Citation Information
Patent Citations
Electrochemical hydrogen-catalyst power system
CN102906925A
BiOBr / ZnAl1.8Fe0.2O4 composite photocatalyst and application thereof
CN108514862A